(x*x)-3x=0

Simple and best practice solution for (x*x)-3x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x*x)-3x=0 equation:


Simplifying
(x * x) + -3x = 0

Multiply x * x
(x2) + -3x = 0
x2 + -3x = 0

Reorder the terms:
-3x + x2 = 0

Solving
-3x + x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-3 + x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-3 + x)' equal to zero and attempt to solve: Simplifying -3 + x = 0 Solving -3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + x = 0 + 3 x = 0 + 3 Combine like terms: 0 + 3 = 3 x = 3 Simplifying x = 3

Solution

x = {0, 3}

See similar equations:

| -2-7=12 | | 1/5x+1/2=3/10x-1 | | a=bx+6x+d | | 4(-2+x)=5(x+.5) | | -3x+6-5=5x+4 | | 8c-9=47 | | 34x+5=175 | | 0=2x^2+11x-9 | | 19x^6-4x^4+11x^3= | | 0=.5x^2+x-2 | | 3x+36=6(x+3) | | -6+13=7x | | 2v^4+3v^3-27v^2= | | 0.1x+2.6x=8-1.8+2.5x | | -3x-2(x+6)+7=7x-9 | | 2(2x+5)-(4x-9)=3(3-4x) | | 12-7b=-2 | | -9x+1=-71 | | -3z=-10 | | 7-5(8-3p)=-123 | | 36r^3-r=0 | | -25=-5+5y | | x*8=-96 | | 6(8+m)=102 | | 4-3e=-2 | | 8x^3+2x^2+4x-5=0 | | 105p=21 | | 2(6-z)-z=2 | | 10y^2-17y+12=y+10 | | v-36=6 | | 36-(3c+4)=2c+7+c | | 2x(6-z)-z=2 |

Equations solver categories